Visual-Spatial and Verbal Remote Association: An fMRI Study - Wu, Ching-Lin; Chen, Hsueh-Chih (Frontiers in Psychology, 2021)
Although idea connections at verbal and conceptual levels have been explored by remote associates tests, the visual-spatial level is much less researched. This study investigated the visual-spatial ability via Chinese Radical Remote Associates Test (CRRAT), wherein respondents consider the positions of the stimulus and target Chinese radicals. Chinese Compound Remote Associates Test (CCRAT) questions also feature stimuli of a single Chinese character; therefore, it was adopted for comparison to distinguish the roles played by verbal and visual-spatial associations in a remote associative process. Thirty-six adults responded to CRRAT and CCRAT; their brain activities were analyzed. Upon excluding the influence of age, verbal comprehension, and working memory, it was found that the caudate, posterior cingulate cortex, postcentral gyrus, and medial frontal gyrus were activated when the respondents answered CCRAT, but only the caudate showed significant activation when they answered CRRAT. The Chinese radical remote association minus the Chinese compound remote association showed that the middle frontal gyrus, inferior parietal lobule, and precuneus demonstrated significant activation. Therefore, this study demonstrated differences in brain mechanisms between visual-spatial and verbal remote associations.